2017
DOI: 10.1007/s00439-017-1793-8
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenic failure and the Y chromosome

Abstract: The Y chromosome harbors a number of genes essential for testis development and function. Its highly repetitive structure predisposes this chromosome to deletion/duplication events and is responsible for Y-linked copy-number variations (CNVs) with clinical relevance. The AZF deletions remove genes with predicted spermatogenic function en block and are the most frequent known molecular causes of impaired spermatogenesis (5-10% of azoospermic and 2-5% of severe oligozoospermic men). Testing for this deletion has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
114
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 164 publications
1
114
0
10
Order By: Relevance
“…Halder et al detected copy number variations (CNVs) in 68 cases of testicular maturation arrest and the AZFc gain was observed in 8.8% of the cases (Halder, Kumar, Jain, & Iyer, ). TSPY1 and TSPY2 are testis‐specific expressed genes, which involves in spermatocyte proliferation and differentiation (Krausz & Casamonti, ). TSPY2 gene gains is also suspected as an aetiological factor with male infertility (Vodicka et al, ), which was observed in 23% of MA cases (Halder et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Halder et al detected copy number variations (CNVs) in 68 cases of testicular maturation arrest and the AZFc gain was observed in 8.8% of the cases (Halder, Kumar, Jain, & Iyer, ). TSPY1 and TSPY2 are testis‐specific expressed genes, which involves in spermatocyte proliferation and differentiation (Krausz & Casamonti, ). TSPY2 gene gains is also suspected as an aetiological factor with male infertility (Vodicka et al, ), which was observed in 23% of MA cases (Halder et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Complete AZFc microdeletions were found with high frequency (5-15%), however, only in genomic DNA samples of infertile men with a severe reduction in sperm number (<10 million per mL ejaculate) and including the OAT syndrome [22,[86][87][88] . These studies clearly show that complete AZFc deletions interfere with the spermatogenic maturation process, reducing its efficiency and causing hypospermatogenesis as the primary mutation effect.…”
Section: Azfc Gene Deletions and Male Infertilitymentioning
confidence: 95%
“…These studies clearly show that complete AZFc deletions interfere with the spermatogenic maturation process, reducing its efficiency and causing hypospermatogenesis as the primary mutation effect. Age-dependent secondary mutation effects might -but must not -eventually cause a complete absence of mature spermatozoa (i.e., azoospermia) in the man's semen fluid [13,88] .…”
Section: Azfc Gene Deletions and Male Infertilitymentioning
confidence: 99%
“…AZFb deletions are mainly associated with germ cell maturation arrest (Costa et al ., ; Soares et al ., ). The most common deletion, in the AZFc region, encompassing DAZ (Deleted in AZoospermia) gene, displays a larger spectrum of clinical and histological manifestations, with variable sperm production capacity; therefore, most of these men show residual spermatogenesis which allows spermatozoa retrieval for in vitro fertilization by intracytoplasmic sperm injection (ICSI) (Vogt et al ., ; Hopps, ; Vogt & Fernandes, ; Pastuszak & Lamb, ; Krausz et al ., ; Goncalves et al ., ; Krausz & Casamonti, ). Furthermore, the AZFc region may be partially deleted (b1/b3, b2/b3 and gr/gr deletions) leading to copy number variations of some genes that play a role in spermatogenesis which results in different amounts of proteins produced and a wide heterogeneity in sperm counts and fertile status depending on the Y genetic background (Fernandes et al ., ; Navarro‐Costa et al ., ; Krausz et al ., ; Colaco & Modi, ).…”
Section: Introductionmentioning
confidence: 99%